GEOPOLITICAL COSMOLOGY: "ELEPHANTS OF EURASIA» - P. L. Karabushenko (Современная наука и инновации, 2022)
The title of this work is derived from the term "geopolitical cosmology" by which we mean the ability of geopolitics to design abstract schemes that clearly explain the essence of their developed geopolitical strategy. This is a kind of test of the logical strength of specific geopolitical doctrines. If they pass this test, they have a future. Otherwise, we are faced with a stillborn doctrine. Analysis of most of these strategies indicates that they were most often intended to intimidate the enemy with their boldness and originality, and other than psychological impact had no practical value. The problem considered in this paper concerns the now widely discussed topic of changing geopolitical poles in the system of world leadership. We are talking about a new geopolitical configuration of Eurasia, where two triangles are built - the Western one (Germany, France, Great Britain) and the Eastern one (Iran, India, China). Both of them are located at different poles of the Russian border and have a certain influence on it. In turn, Russia itself becomes the main geopolitical participant in these international relations, which it exerts a specific influence on, realizing its national interests. It is Russia, in our opinion, that plays a unifying role, ensures the establishment of an equilibrium partner dialogue between East and West, which should meet in accordance with the international agenda formulated by Russia and the proposed picture of the world.